Chatbot Artificial Intelligence as Educational Tools in Science and Engineering Education: A Literature Review and Bibliometric Mapping Analysis with Its Advantages and Disadvantages - Al Husaeni, Dwi Fitria; Haristiani, Nuria; Wahyudin, W.; Rasim, R. (ASEAN Journal of Science and Engineering, 2024)
This research was conducted to analyze the application, utilization or use of AI chatbots in the education sector based on several previous studies. Bibliometric analysis is used to identify the current status of research and critical points in bibliometric data mapping can help predict future research trends. Data searches were carried out on the Scopus database with the keywords "Chatbot" AND "education" with a research year range of 2007-2024. There were 376 articles found. The research results show that research on chatbots, especially in the education sector, is increasingly in demand. In 2023 there will be a drastic increase in the number of studies regarding chatbots in the education sector compared to previous years. This is because chatbots are considered to be an interesting tool to use in education because they enable a more innovative teaching process in terms of improving learning processes and outcomes. There are 25 countries that have contributed to related research, with the United States, Australia, United Kingdom, China and Taiwan in the top five. This research also shows that there are 26 subject areas that have used chatbots in the education sector. The use of chatbots in the education sector has advantages and disadvantages. With the completion of this research, it is hoped that it can become material for consideration for related research.